Shariah Framework of Banking laws based on the Opinions of Jurists of the Guardian Council - Seyed Hassan Heidari; Mohammad Rasul Fakhreh; Mohammad Ali Farahani (دانش حقوق عمومی)
Studying and explaining the approach of the jurists of the Guardian Council in examining banking regulations and related legislation, in addition to theoretical benefits, can familiarize ordinary legislators with the perspective of this institution regarding the Sharia framework of banking laws. Consequently, by assisting lawmakers in drafting banking laws, it can shorten and expedite the legislative process due to reduced back-and-forth between the Parliament and the Guardian Council. The main question of this research is to examine the practices of the Guardian Council and extract instances where the jurists of this council have deemed banking regulations incompatible with Sharia principles. Based on descriptive-analytical research, the jurists of the Guardian Council have identified several issues in their Sharia review of the banking regulations of the Islamic Consultative Assembly, including: 'expedited judicial proceedings for specific lawsuits,' 'limitations on legal complaints against supervised credit institutions,' 'the inability to annul or invalidate the actions of the supervisory board,' 'enumerating the duties of the Central Bank Governor and exercising the Central Bank's powers without adherence to laws and Sharia principles,' 'using endowment properties without regard to the endowment deed,' 'the lack of Sharia and judicial competence of non-judicial authorities,' 'the absence of conditions of trustworthiness and honesty for banking officials,' 'the impossibility of judicial objection and litigation,' 'absolute surveillance and access to individuals' information,' 'contrary to public interests,' 'retroactive application of rulings,' 'usury,' and 'disproportionate crime and punishment.' Therefore, it is necessary for the legislator to pay attention to these mentioned jurisprudential objections while drafting banking laws.